Managing the transition of learners from foundation to intermediate phases in Mashishing, Mpumalanga Province - Mangena, Flora (My University, 2021)
The purpose of the study was to examine how the transition process from the foundation to the intermediate phases could be properly managed to minimise challenges that are part of it, some of which disturb a smooth integration into the intermediate phase. This is a qualitative case study which employed interviews, document review and observation methods to collect data. Data were analysed through the thematic content analysis and the constant comparative methods. Findings of the study revealed amongst others that shifting of language of instruction from mother tongue in the foundation phase to English in the intermediate phase requires attention. In addition, changed teachers’ handwritings from foundation to intermediate gave learners a problem. Finally, teachers who were not trained to teach a foundation phase were found to be complicating the transition from the foundation to the intermediate phases by learners. On the basis of the shared findings, the researcher recommends that English be made a language of instruction from the foundation phase, not from the intermediate phase as it is the currently the case in primary schools The researcher further, recommends that it be made mandatory for teachers from the foundation and intermediate phases to use print method when writing inside the classroom with learners as a way of addressing the problem of different handwritings by teachers. Some of teachers’ handwritings give learners a huge problem to see clearly. Hence the recommendation of the print method. Finally, the researcher strongly recommends that only well trained and qualified teachers be permitted to teach foundation and intermediate phases. This is likely to ascertain that a good educational foundation is laid at an early stage, when learners are still so young and cognitively highly receptive.
Thesis (M. Ed. (Education Studies)) -- University of Limpopo, 2021
Keywords: Transition; Foundation phase; Intermediate phase; Managing; Classroom management -- South Africa -- Mpumalanga; Classroom environment -- South Africa -- Mpumalanga; Teaching -- South Africa -- Mpumalanga